Concurrent evaluation of visual, cytological and HPV testing as screening methods for the early detection of cervical neoplasia in Mumbai, India - Surendra S. Shastri; Ketayun Dinshaw; Geetanjali Amin; Smriti Goswami; Sharmila Patil; Roshini Chinoy; S. Kane; Rohini Kelkar; Richard Muwonge; Cédric Mahé; Dulhan Ajit; R. Sankaranarayanan (The World Health Organization, 2005)
OBJECTIVE: Naked eye visual inspection with acetic acid (VIA), magnified VIA (VIAM), visual inspection with Lugol's iodine (VILI), cytology and human papillomavirus (HPV) testing were evaluated as screening methods for the detection of high-grade squamous intraepithelial lesions (HSIL) of the uterine cervix in a cross-sectional study in Mumbai, India. METHODS: Cytology, HPV testing, VIA, VIAM and VILI were carried out concurrently for 4039 women aged 30-65 years. All women were investigated with colposcopy and biopsies were taken from 939 women who had colposcopic abnormalities. The reference standard for final disease status was histology or negative colposcopy. The presence of HSIL was confirmed in 57 women (1.4%). The test characteristics for each method were calculated using standard formulae. RESULTS: The sensitivities of cytology, HPV testing, VIA, VIAM and VILI were 57.4%, 62.0%, 59.7%, 64.9%, and 75.4%, respectively (differences were not statistically significant). The specificities were 98.6%, 93.5%, 88.4%, 86.3%, and 84.3%, respectively. Adding a visual test to cytology or HPV testing in parallel combination resulted in a substantial increase in sensitivity, with a moderate decrease in specificity. The parallel combination of VILI and HPV testing resulted in a sensitivity of 92.0% and a specificity of 79.9%. CONCLUSION: As a single test, cytology had the best balance of sensitivity and specificity. Visual tests are promising in low-resource settings, such as India. The use of both VIA and VILI may be considered where good quality cytology or HPV testing are not feasible. The sensitivity of cytology and HPV testing increased significantly when combined with VIA or VILI.